2009
DOI: 10.7205/milmed-d-00-1109
|View full text |Cite
|
Sign up to set email alerts
|

Educational Preferences and Outcomes From Suicide Prevention Training in the Veterans Health Administration: One-Year Follow-Up With Healthcare Employees in Upstate New York

Abstract: This study identifies training outcomes and educational preferences of employees who work within the Veterans Health Administration (VHA). Using a longitudinal pre-postsurvey design, 71 employees from one geographic region of VHA healthcare facilities participated in an evaluation of a brief standardized gatekeeper program and a needs assessment on training preferences for suicide and suicide prevention. Results indicate significant differences in knowledge and self-efficacy from pre to post (p < 0.001), altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…Findings reveal that this population tends to have a high degree of experience with suicide, both personally and professionally. Compared to previous literature, Matthieu et al (2009) found that 94.3% ( n = 71) of VA employees had contact with suicidal individuals, which is consistent with the sample in the current study. This finding may be due to the way in which the current sample was selected, targeting community and clinical providers, particularly those within the VA who worked specifically in mental health or who were suicide prevention coordinators.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Findings reveal that this population tends to have a high degree of experience with suicide, both personally and professionally. Compared to previous literature, Matthieu et al (2009) found that 94.3% ( n = 71) of VA employees had contact with suicidal individuals, which is consistent with the sample in the current study. This finding may be due to the way in which the current sample was selected, targeting community and clinical providers, particularly those within the VA who worked specifically in mental health or who were suicide prevention coordinators.…”
Section: Discussionsupporting
confidence: 91%
“…Four of the five sections of the suicide and suicide prevention self-report survey instrument have been utilized in previous research (Matthieu et al, 2008, 2009). These sections include: (1) Organizational assessment, (2) Provider demographics, (3) Individual-level factors, (4) Exposure to suicide, and (5) Awareness of suicide prevention resources.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey packet used in previous gatekeeper studies (Matthieu, Cross, Batres, Flora, & Knox, 2008;Matthieu et al, 2009) contained five sections:…”
Section: Methodsmentioning
confidence: 99%
“…This particular QPR program, with the addition of a research tested behavioral rehearsal component, has been studied extensively with positive findings for increased knowledge and self efficacy among adults working in an academic medical center department of psychiatry, VA health care facilities, and on college campuses (Cross, Matthieu, Cerel, & Knox, 2007;Cross, Matthieu, Lezine, & Knox, 2010;Matthieu, Chen, Schohn, Lantinga, & Knox, 2009). The unique feature of this particular gatekeeper training program are these studies supporting the use of the behavioral rehearsal in both individual and groups settings.…”
Section: Introductionmentioning
confidence: 98%